Etis Teologis Keteladanan Guru Pendidikan Agama Kristen Bagi Peserta Didik - Selfiana Carolina Adu; Andreas Fernando; Reni Triposa (APOSTOLOS, 2022)
Technology advances in 21th Century are accompanied by the increasement of child violence cases. Bullying and moral decadency occur among students. Christian education teacher’s role as model of character is needed by the students to able to change their behavior and achieve the goal of Christian Education, namely knowing and experiencing God. Student’s behavior changes are very influenced by teacher’s personality and character. The examples teacher shows every day will affect student’s behavior change. Christian education teacher must imitate the examples are given by Jesus the Great Teacher. Christian education teacher who has a “born again” experience and keep struggling in doing the truth of God’s Word every day through Holy Spirit’s guidance could influence student’s behavior. Teachers’ examples risen by their daily spirituality growth, because teaching is not only matter of knowledge transferring from a head to a head, but from a heart to a heart of the teacher to the students.